2022
DOI: 10.1097/sle.0000000000001041
|View full text |Cite
|
Sign up to set email alerts
|

Overall Complications Following Robotic Heller Myotomy Are Lower Compared With Laparoscopy

Abstract: Background: The use of robotics in foregut surgery has become more prevalent in the United States over the last 10 years. We sought to find the differences in the clinical outcomes of robotic surgery compared with traditional laparoscopy in patients undergoing Heller myotomy. Materials and Methods: A retrospective population-based analysis was performed using the National Inpatient Sample (NIS) database for the span of 2010 to 2015. All patients who underwent laparoscopic or robotic Heller myotomy were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Other published literature does not report significant differences in length of stay (LOS) when comparing RHCM with LHCM. 19 23 , 34 , 35 However, in the present cohort, 12/13 patients were discharged as either day cases or had a single overnight stay. We believe that the reduced risk of oesophageal perforation has increased our team’s confidence in early discharge of these patients.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Other published literature does not report significant differences in length of stay (LOS) when comparing RHCM with LHCM. 19 23 , 34 , 35 However, in the present cohort, 12/13 patients were discharged as either day cases or had a single overnight stay. We believe that the reduced risk of oesophageal perforation has increased our team’s confidence in early discharge of these patients.…”
Section: Discussionmentioning
confidence: 86%
“… 32 34 A retrospective review of the USA National Inpatient Sample of patients undergoing RHCM was associated with increased cost (US$42,900 vs US$34,300) when compared with LHCM. 35 Another publication from the USA has also demonstrated that LHCM is significantly cheaper than RHCM (US$7,441±7,897 vs US$9,415±5,515). 34 Although cost reduction strategies are likely to arise with the increasing utilisation of robotics, 32 , 34 , 36 at present the robotic approach should be considered to be more expensive.…”
Section: Discussionmentioning
confidence: 99%
“…[19] A population-based analysis revealed that even in high-volume centers, average length of stay is shorter with the robotic approach although average cost Is elevated. [24] Data on robot-assisted hiatal hernia repair also show excellent results regarding safety and perioperative outcomes even in technically demanding cases [25][26][27][28]. Results regarding postoperative complications are currently inconclusive, as certain studies comparing the laparoscopic and robotic approaches for hiatal hernia repair present dominance of the robotic approach, while others report increased incidence of respiratory complications in patients who undergo robotic repair [29,30].…”
Section: Discussionmentioning
confidence: 99%